Supraorbital foramen and supraorbital notch morphometry- An assured aid to target the supraorbital nerve - Kumar, Naveen; Bhaskar, Ravi; S, Anjana; KS, Satheesha; Shetty D, Surekha; Aithal P, Ashwini (Bangladesh Journal of Medical Science, 2023)
Introduction: Supraorbital neuralgia is manifested with pain and tenderness at the distribution of the supraorbital nerve (SN). Explicit knowledge of the location of SN is vital for clinicians performing regional nerve blocks to relieve the pain. In the present study, detailed measurements of the supraorbital foramen (SOF) and supraorbital notch (SON) of South Indian skulls are presented, and the data are compared with those from other populations. Methodology: One hundred SON/SOF were assessed morphometrically from 50 dried adult human skull. Relevant morphometric measurements were performed using Vernier caliper. The parameters used were horizontal and vertical diameters of SON/SOF, distance between SON/SOF from the supraorbital rim; SOF to the nasal skeletal midline; SOF to the temporal crest of the frontal bone, and SOF to the superior wall of the IOF. Data was analyzed using SPSSv16.0. Results: SON was more frequently found than SOF. The mean distance of SON/SOF to the nasal midline was 24.77 mm on right side and 23.36 mm on left side. The mean distance of SON/SOF to the temporal crest of frontal bone was 30.22 mm on both sides. Mean distance between SON/SOF to infraorbital foramen was 39.71 mm on right side and 40.41 mm on left side. Mean height of SOF was 1.38 mm on the right side and 1.31 mm on the left side. Mean transverse diameter of SON was 3.93 mm. Conclusion: Differences exist in the dimensions and position of SOF/SON among different races and people of other regions. Anatomical knowledge of SON/ SOF is essential in facilitating craniofacial surgical procedures and in the treatment of neuralgia. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 598-603